Facebook in the University Workplace. Issue 1 (November 2013) - Francois, Aurora; Hebbani, Aparna; Rintel, Sean
Access to social network sites (SNS) in the workplace has been much debated. While some consider SNS a distraction, others consider them a tool for professional socialisation and that recreational access positively impacts satisfaction. This exploratory study reports results from an online survey of employees from one faculty of an Australian university, exploring how they used Facebook at work and how they would react to a hypothetical Facebook ban. Three-quarters of respondents used Facebook at work, primarily for personal socialisation during breaks. Many self-imposed a strict personal/professional separation, but opposed a hypothetical SNS ban, perceiving it as an infringement on their workplace autonomy. It is argued that university employees – academic and professional – can be trusted to self-regulate access.